Lung Hyaluronasome: Involvement of Low Molecular Weight Ha (Lmw-Ha) in Innate Immunity - Antony Hoarau; Myriam Polette; Christelle Coraux (Biomolecules, 2022)
Hyaluronic acid (HA) is a major component of the extracellular matrix. It is synthesized by hyaluronan synthases (HAS) into high-molecular-weight chains (HMW-HA) that exhibit anti-inflammatory and immunomodulatory functions. In damaged, infected, and/or inflamed tissues, HMW-HA are degraded by hyaluronidases (HYAL) or reactive oxygen species (ROS) to give rise to low-molecular-weight HAs (LMW-HAs) that are potent pro-inflammatory molecules. Therefore, the size of HA regulates the balance of anti- or pro-inflammatory functions. The activities of HA depend also on its interactions with hyaladherins. HA synthesis, degradation, and activities through HA/receptors interactions define the hyaluronasome. In this review, a short overview of the role of high and low-molecular-weight HA polymers in the lungs is provided. The involvement of LMW-HA in pulmonary innate immunity via the activation of neutrophils, macrophages, dendritic cells, and epithelial cells is described to highlight LMW-HA as a therapeutic target in inflammatory respiratory diseases. Finally, the possibilities to counter LMW-HA’s deleterious effects in the lungs are discussed.